2013
DOI: 10.1002/poc.3101
|View full text |Cite
|
Sign up to set email alerts
|

Conformational diversity and dynamics of distally disubstituted calix and thiacalix[4]arenes in solution

Abstract: According to the quantum chemical calculations and Dynamic NMR experiments in the distally disubstituted classical and thiacalix[4]arenes (CCA and TCA) in addition to the C 2v symmetrical pinched cone (PC) conformation, the distorted cone (DC) form with an approximate C s overall symmetry (with two OH groups bonded to one oxygen atom) also corresponds to the energy minimum. Moreover, in DC form, two different mutual orientations of O-R groups at a lower rim lead to two stable conformations: the first -with bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Given low yields of thiacalixcrowns 2b,c , alkyl fragments were firstly attached to compound 1 to access type-II/III ligands. Dialkylated products 3 and 4 were synthesized as reported previously [ 26 , 27 ] and further reacted with the glycols ( Scheme 1 ). Type-II/III crown-ethers 5b,c and 6b,c were isolated in low yields (12–32%), while yields of crown-4 5a and 6a were 75% and 39%, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given low yields of thiacalixcrowns 2b,c , alkyl fragments were firstly attached to compound 1 to access type-II/III ligands. Dialkylated products 3 and 4 were synthesized as reported previously [ 26 , 27 ] and further reacted with the glycols ( Scheme 1 ). Type-II/III crown-ethers 5b,c and 6b,c were isolated in low yields (12–32%), while yields of crown-4 5a and 6a were 75% and 39%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Water was deionized on an Adrona Crystal purification system up to the conductivity of 0.055 µS/cm. Known procedures were employed to synthesize p-tertbutylthiacalix [4]arene 1 [56], dialkylated thiacalixarenes 3 [26] and 4 [27], and thiacalixcrowns 2a-c [24] and 6a-c [13,25].…”
Section: Methodsmentioning
confidence: 99%
“…We found that it is general observation for distal disubstituted thiacalix [4]arene derivatives. 27,28 Moreover, this is completely different from the behavior of disubstituted classical calix [4]arene (C[4]A) derivatives, 29 in which both O-R fragments are xed by intramolecular hydrogen bonding resulting in the rigid cup-shaped structure.…”
mentioning
confidence: 85%
“…It could distinguish cone and 1,3-alternate stereoisomeric forms possessing identical splitting patterns of NMR signals. In the former case, two diagonal aryl rings impose a shielding ring current effect on neighboring aryl rings, resulting in their significant upfield shift and a large spacing between these signals [18,19]. The ring current effect is impossible in the 1,3-alternate stereoisomeric form, and the aryl signals are located close to each other.…”
Section: Synthesis and Characterization Of Ligandsmentioning
confidence: 99%